2003
DOI: 10.1002/art.10979
|View full text |Cite
|
Sign up to set email alerts
|

Frequent infection with a viral pathogen, parvovirus B19, in rheumatic diseases of childhood

Abstract: Objective. To find further evidence of the association of parvovirus B19 infection with juvenile rheumatic diseases, and to get new insights into the immunopathogenesis of these diseases.Methods. Paired serum and synovial fluid samples from 74 children with rheumatic disease were analyzed with respect to their content of viral DNA and antibodies directed against the B19 viral proteins VP1, VP2, and NS1. Control sera from 124 children with noninflammatory bone diseases or growth retardation were also analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…These figures are similar to those from Cohen and Buckley, who reported a rate of 70-80% in a healthy population at an age of 40 years [2]. Similar frequencies have also been reported in children with rheumatic diseases [15].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These figures are similar to those from Cohen and Buckley, who reported a rate of 70-80% in a healthy population at an age of 40 years [2]. Similar frequencies have also been reported in children with rheumatic diseases [15].…”
Section: Discussionsupporting
confidence: 85%
“…Compared to a healthy population of young adults, with a seroprevalence of 22%, this is a remarkable difference [9,23]. Elevated prevalences of NS-1 antibodies were also found in patients with rheumatic PanU [2,9,22,23] [9,15]. It has been previously shown that antibodies against NS-1 are produced in long-standing or persistent infections with a higher incidence of infection of mainly non-permissive cells (thrombocytes and white blood cells), resulting in permanent destruction of these cells.…”
Section: Discussionmentioning
confidence: 76%
“…Due to viral replication in the erythroid progenitor cells, severe or lifethreatening diseases can occur in immunocompromised patients and in individuals with shortened red cell survival (Brown et al, 1984;Kurtzman et al, 1988;Pattison et al, 1981;Public Health Laboratory Service, 1990;Skjöldebrand-Sparre et al, 2000). Besides the typical features, B19V is implicated in a wide spectrum of illnesses including neurological, cardiac, hepatic and rheumatological disorders (Broliden et al, 2006;Kerr et al, 2002;Lehmann et al, 2003;Young & Brown, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…B19 is the causative agent of erythema infectiosum (fifth disease), hydrops fetalis, and transient aplastic anemia (1,86). Several studies disclosed an association between B19 and a variety of diseases (43,48,63,80), such as arthritis (56, 77), vasculitic syndromes (19, 24, 31, 80), hepatitis (27,36,38,75,85), and neurological disorders (2, 85). Specifically, B19 infections have been observed to be associated with acute and chronic myocarditis (13,16,30,44,53,(58)(59)(60)71).…”
mentioning
confidence: 99%